The role of Mesogenin1 in the dynamics of movement and differentiation of mesoderm progenitor cells - Figueira, Ana Margarida da Silva, 1990- (2013)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2013